The influence of democratic school management on the work of pedagogical coordination - Rocha , Aline Barros da; Abreu, Charles Pereira de (Seven Editora, 2024)
Democratic school management plays a crucial role in the effectiveness of the work of pedagogical coordination The accomplishment of this research is relevant because it included investigating what democratic school management is, emphasizing its influence on the performance of pedagogical coordination in schools. Through a literature review, the impact of the participation of the various actors of the school community in decision-making, in the promotion of autonomy and in the establishment of a collaborative culture is examined. Democratic management favors the exchange of experiences, dialogue and the collective construction of educational projects, strengthening the role of pedagogical coordination as a mediator between the demands of the community and educational practices. In addition, it addresses how democratic leadership contributes to the professional development of pedagogical coordinators, encouraging reflection and continuous improvement of their practices. Finally, this article was an experience that served to expand the knowledge about the importance of democratic school management for the work of pedagogical coordination, seeking to understand how these strategies influence the management process and the quality of the education offered. DOI:https://doi.org/10.56238/sevened2024.009-023